2020
DOI: 10.4081/monaldi.2020.1153
|View full text |Cite
|
Sign up to set email alerts
|

The brain-heart connection: a multiple sclerosis relapse presenting as Takotsubo Syndrome. A case report and literature review

Abstract: We hereby report a puzzling case of multiple sclerosis (MS) relapse presenting as Takotsubo syndrome (TTS). Female, 42-years old, who presented herself to the Emergency Room of University Hospital “ASST Spedali Civili” of Brescia, Italy, for a severe headache and a non-ST-segment elevation acute coronary syndrome. Coronary angiogram showed no signs of coronary atherosclerosis. Upon further neurological evaluation, a diagnosis of MS relapse, related to TTS, was made, and treatment was started accordingly. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The triggers and background factors for RCVS include the postpartum period, migraine, hypertension, use of some drugs such as α-agonists, serotonin agonists, abuse of illicit drugs [2], rapid rise in Hb levels [3], and temperature differences such as bathing and showering with too cold or hot water [4]. In addition, it has been reported that RCVS worsens immediately after its onset by administration of steroids (which was in the history of our patient, as acute demyelinating encephalomyelitis had been suspected) [11]. Also, in our case, infections, vasculitis, and collagen diseases were excluded from clinical findings and blood test results.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The triggers and background factors for RCVS include the postpartum period, migraine, hypertension, use of some drugs such as α-agonists, serotonin agonists, abuse of illicit drugs [2], rapid rise in Hb levels [3], and temperature differences such as bathing and showering with too cold or hot water [4]. In addition, it has been reported that RCVS worsens immediately after its onset by administration of steroids (which was in the history of our patient, as acute demyelinating encephalomyelitis had been suspected) [11]. Also, in our case, infections, vasculitis, and collagen diseases were excluded from clinical findings and blood test results.…”
Section: Discussionmentioning
confidence: 68%
“…We did not perform the coronary angiography to avoid the adverse effect such as vasoconstriction by the contrast medium; however, coronary vasospasm may have occurred by the mechanism like that of cerebral vasospasm. Whilst, based on the UCG findings and ECG changes that cannot be explained by the distribution of coronary arteries, catecholamine cardiomyopathy such as reverse Takotsubo cardiomyopathy may have occurred by severe pain from thunderclap headache [11].…”
Section: Discussionmentioning
confidence: 99%
“…The NCCM can be grouped into seven phenotypical subtypes (3), among which our case is associated with LV dilation and dysfunction at baseline. The interaction between MS relapses and myocardial stunning through a sympathetic outburst has been proposed, similar to what occurs in stress cardiomyopathy, where it has been found in common that demyelinating lesions compromise the medulla oblongata that controls the neurovegetative cardiovascular center (10). Unlike this, in our patient, the demyelinating lesions found (Figures 1A-C) did not affect the brainstem that includes the medulla oblongata; therefore, we rule out this alternative hypothesis to explain the reduced LVEF in our case, and we suggest that this is probably due to the advancement of the NCCM itself.…”
Section: Discussionmentioning
confidence: 80%
“…Finally, some recently-published data also suggested a link between an oncologic process and TTS, as almost 10% of TTS patients seem to develop cancer in a 4-year follow-up ( 20 ). MS however has only been identified as the trigger of TTS in a few case reports across the scientific literature ( 5 , 11 , 12 , 16 ), and even less so as the trigger of reverse TTS ( 7 , 8 , 10 , 11 , 21 27 ). To date, no specific treatment has been shown to improve clinical outcomes ( 3 5 ).…”
Section: Discussionmentioning
confidence: 99%